Kesadaran Diri Qurani Melalui Metode Atomic Habits Dalam Membangun Karakter Spiritual - Kholilurrohman Kholilurrohman; Abdullah Safei; Nasaruddin Umar (ZAD Al-Mufassirin, 2022)
This paper describes that Quranic self-awareness can build spiritual character through the atomic habits method from the life habits of each individual. These habits can be built through the smallest things (atomic) which are underestimated by each individual. With the ability of each individual to observe his own weaknesses, it is possible to place himself in time (present, past, and future). With this ability, a person can plan his actions in the future through the smallest things in the habit of his life.